Physical activity levels and energy intake according to the presence of metabolic syndrome among single-household elderly in Korea: Korean National Health and Nutrition Examination Survey 2016–2018 - Sung, Eun-Sook; Park, Jonghoon (Frontiers in Public Health, 2023)
Background Exercise and dietary and nutritional intake affect the risk and prevalence of metabolic syndrome (MetS) in elderly people, effects that may differ according to sex in elderly single households (ESH). This study aimed to analyze the differences in physical activity (PA) levels and energy intake according to sex and prevalence of MetS among elderly people in Korea to investigate the relationships between these factors. Methods Data from 893 elderly individuals (aged >65 years) were obtained from the Korean National Health and Nutrition Examination Survey (2016–2018). We analyzed PA levels (occupational and recreational PA and place movement) and energy intake (EI; total, carbohydrate, protein, and fat), and found that there were sex differences in both according to the presence or absence of MetS in ESH. Results Among both males and females, the MetS group had a significantly lower recreational moderate PA than the non-MetS group. However, total PA in males was significantly higher in the non-MetS than in the MetS group, but there was no significant difference in females. Furthermore, the EI of females did not differ in the presence or absence of MetS, except for fat intake, and in the nutritional intake of ESH in males, no difference was found in the presence or absence of MetS. We also found that in Odd ratio, “active” was associated with lowering high waist circumference (OR = 0.40, 95%CI = 0.21–0.76), and “very active” was associated with lower MetS occurrence (OR = 0.51, 95%CI = 0.33–0.81) and low high-density lipoprotein cholesterol (HDL-C) (OR = 0.55, 95%CI = 0.37–0.83). Conclusions Therefore, in the MetS group of ESH, there was a significant correlation of the MetS component in PA rather than EI. Male ESH require interventions that increase PA, while female ESH require nutrition interventions that increase and balance PA. Therefore, a new program is needed that promotes continuous interest and healthy lifestyles in consideration of the characteristics of ESH.